Analisis Kontrastif Konstruksi Kalimat [kaverba] dalam Bahasa Sunda dengan [-rareru] dalam Bahasa Jepang - Sidiq, Inu Isnaeni; Suherman, Agus; Ampera, Taufik (Journal of Japanese Language Education and Linguistics, 2018)
Basa Sunda and Japanese language have so many similiratity in terms of passive expressions. Both language recognize direct passive utterance and indirect passive utterance. This paper analyzes indirect passive construction of basa Sunda and contrast them to similar construction in Japanese. This paper show that from four of the basa Sundaâs indirect passive construction functions, only two of them comply to the Japanese indirect passive construction semantically. These functions are spontaneus clause (jihatsu) and potential clause (kanou). Despite of the semantic similarity, this paper also show that these type of indirect passive can be constructed from intransitive verbs in both language. Keyword : indirect passive; jihatsu;kanoubun;impersonal passive